Alumni Association hosts cap decorating party, May 14 - Uribes, Tom::::::::: (2013)
Graduating students wanting to graduate in style at Fresno State's Commencement next week can join the Cap Decorating Party, 4-7 p.m. May 14 in the Smittcamp Alumni House.